Hereditary pulmonary arterial hypertension burden in pediatrics: A single referral center experience - Ishizuka, Maki; Zou, Wenxin; Whalen, Elise; Ely, Erin; Coleman, Ryan D.; Lopez-Terrada, Dolores H.; Penny, Daniel J.; Fan, Yuxin; Varghese, Nidhy P. (Frontiers in Pediatrics, 2023)
Introduction: Hereditary pulmonary arterial hypertension (HPAH) is a rare yet serious type of pulmonary arterial hypertension (PAH). The burden in the pediatric population remains high yet underreported. The objective of this study is to describe the distribution of mutations found on targeted PAH panel testing at a large pediatric referral center. Methods: Children with PAH panel administered by the John Welsh Cardiovascular Diagnostic Laboratory at Texas Children’s Hospital and Baylor College of Medicine in Houston, Texas between October 2012 to August 2021 were included into this study. Medical records were retrospectively reviewed for clinical correlation. Results: Sixty-six children with PAH underwent PAH genetic testing. Among those, 9 (14%) children were found to have pathogenic mutations, 16 (24%) children with variant of unknown significance and 41 (62%) children with polymorphism (classified as likely benign and benign). BMPR2 mutation was the most common pathogenic mutation, seen in 6 of the 9 children with detected mutations. Hemodynamic studies showed higher pulmonary vascular resistance among those with pathogenic mutations than those without (17.4 vs 4.6 Wood units). All children with pathogenic mutations had severe PAH requiring triple therapy. There were tendencies for higher lung transplantation rate but lower mortality among those with pathogenic mutations. Conclusions: Abnormalities on genetic testing are not uncommon among children with PAH, although majority are of unclear significance. However, children with pathogenic mutations tended to present with more severe PAH requiring aggressive medical and surgical therapies. Genetic testing should be routinely considered due to consequences for treatment and prognostic implications. Larger scale population studies and registries are warranted to characterize the burden of HPAH in the pediatric population specifically.